2020
DOI: 10.3390/biomimetics5040059
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Honeycomb Core Design: An Experimental Study of the Role of Corner Radius, Coping and Interface

Abstract: The honeybee’s comb has inspired the design of engineering honeycomb core that primarily abstract the hexagonal cell shape and exploit its mass minimizing properties to construct lightweight panels. This work explored three additional design features that are part of natural honeybee comb but have not been as well studied as design features of interest in honeycomb design: the radius at the corner of each cell, the coping at the top of the cell walls, and the interface between cell arrays. These features were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…H oneycomb is hailed as the pinnacle of biological architecture for its ability to maximize storage area while minimizing building material (1)(2)(3)(4). In the 4th century, Pappus of Alexandria marveled at the "geometrical foresight" of the bees, while Darwin dubbed it "the most wonderful of all known instincts" (5,6).…”
mentioning
confidence: 99%
“…H oneycomb is hailed as the pinnacle of biological architecture for its ability to maximize storage area while minimizing building material (1)(2)(3)(4). In the 4th century, Pappus of Alexandria marveled at the "geometrical foresight" of the bees, while Darwin dubbed it "the most wonderful of all known instincts" (5,6).…”
mentioning
confidence: 99%
“…To shape the wax, it is likely that the bees increase the local temperature with their thoraxes [ 31 ] and then compressing it with their mandibles, [ 32 ] to the desired wall thickness. Previous work by Gross et al [ 33 ] suggested the possibility that the coping could be used as a means to prevent the fraying of the open edges of the hexagonal cell mitigating every day wear and tear as the bees go about entering and leaving the cell. Another function that the coping serves might be the retention of honey and nectar within the cell by providing a slight ramp at the rims of the cell reducing its diameter, thus preventing stored liquids from flowing out.…”
Section: Resultsmentioning
confidence: 99%
“…The coping is a bulb-like structure present at the outer rims of a hexagonal honeycomb cell and can be easily identified due to it being thicker than the wall segment to which it is attached. [3,29,30] The coping forms out of the mounds on the troughs as the bees begin to compress and densify the material just behind the location where new material is added (Figure 3c). This structure is ubiquitous at all the locations on the comb where there is a potential to grow.…”
Section: Mechanisms Of Formation For a Single Honeycomb Cellmentioning
confidence: 99%
“…However, perception via these receptors is limited. Although the structure of three-rhombus cells is not complex, bees are still unable to construct rhombuses with obtuse and acute angles at theoretical optima (109° 28′ and 70° 32′, respectively) (Goss et al 2020).…”
Section: Dihedral and Plane Angles Of Fejes Tóth Cellsmentioning
confidence: 99%